Zakat-based e-philanthropy strategy in global humanitarian diplomacy: a case study of BAZNAS’ #MembasuhLukaPalestina program - Khusni Mubarok (Journal of Islamic Economics Management and Business (JIEMB), 2025)
The humanitarian crisis in Palestine has spurred the emergence of digital-based donation collection innovations in Indonesia, with the National Zakat Amil Agency (BAZNAS) serving as a key actor through its #MembasuhLukaPalestina (#WashAwayPalestinesWounds) program, an initiative in e-philanthropy aimed at responding to global humanitarian tragedies. This article seeks to analyze BAZNAS’s zakat-based e-philanthropy strategy and evaluate its effectiveness in collecting and distributing donations through digital platforms as part of global humanitarian diplomacy. Employing a qualitative descriptive method with a case study approach, data were collected through in-depth interviews, digital observation, media documentation, and analysis of official BAZNAS documents, which were then processed using Miles and Huberman’s interactive analysis model. BAZNAS’s strategy of leveraging digital platforms –such as websites, social media, and e-commerce– has proven effective in accelerating fundraising, expanding public participation, and enhancing transparency. Compared to conventional methods, the digital system is more efficient, accountable, and less prone to misuse. The program not only increases zakat collection but also positions zakat as a strategic instrument in global humanitarian diplomacy grounded in Islamic economics. This model demonstrates that zakat can transform into a cross-border solidarity force through digitalization. BAZNAS’s e-philanthropy strategy exemplifies the concrete integration of Islamic values and technology in strengthening an Islamic economic system based on solidarity, efficiency, and social justice.